Conceptualization and Elaboration of a Teaching Unit on Digital Twins in Geometrical Variations Management - Schleich, Benjamin; Roth, Martin; Schächtl, Paul (Procedia CIRP, 2022)
Driven by the steadily increasing digitization of design and manufacturing, digital twins, which describe the tight connection of models from design with data streams from manufacturing and product operation, are becoming more and more important. Particularly in geometrical variations management, digital twins can be used beneficially, for example, to identify joining partners that fit together ideally despite geometrical deviations, thereby reducing manufacturing costs and increasing product quality. Motivated by the increasing importance of these approaches with a simultaneous lack of training offers for this, a teaching unit was developed, which aims at students acquiring competencies for the independent development of a digital twin and its exemplary use in geometrical variations management. The paper describes the conceptualization and elaboration of this teaching unit on digital twins in geometrical variations management and carves out opportunities for its further improvement.<br